Sanctuary Cinema : Origins of the Christian Film Industry. - Lindvall, Terry (NYU Press, 2007)
Winner of the Religious Communication Association Book of the Year Award for 2008. Sanctuary Cinema provides the first history of the origins of the Christian film industry. Focusing on the early days of film during the silent era, it traces the ways in which the Church came to adopt film making as a way of conveying the Christian message to adherents. Surprisingly, rather than separating themselves from Hollywood or the American entertainment culture, early Christian film makers embraced Hollywood cinematic techniques and often populated their films with attractive actors and actresses. But t.